The Impact of Disease Activity on Hematological Parameters among Rheumatoid Arthritis Patients: A Cross-Sectional Analysis - Mohsen, Rana; Hajar khaled Masser,; Mostafa Nuhad Al daraji, (University of Thi-Qar Journal of Science, 2025)
ABSTRACT:Background: “Rheumatoid arthritis (RA) is a systemic autoimmune disorder primarily marked by persistent inflammation of the synovial joints, often accompanied by extra-articular involvement that can affect multiple organ systems. Although extensive research has investigated inflammatory and hematological parameters among Iraqi RA patients, there is still a significant gap in region-specific data, particularly concerning patients from Anbar Governorate.Objectives: “This investigation sought to assess and compare the concentrations of key inflammatory and immunological markers—including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), rheumatoid factor (RF), anti-cyclic citrullinated peptide (Anti-CCP) antibodies, white blood cell (WBC) count, as well as interleukins IL-17 and IL-21—between patients diagnosed with rheumatoid arthritis and healthy individuals residing in Anbar, Iraq. Methods: A case-control study was conducted involving 50 RA patients and 40 healthy controls. Hematological and immunological markers (ESR, CRP, RF, Anti-CCP, WBC) were measured using routine laboratory techniques, while IL-17 and IL-21 were quantified using ELISA. Statistical significance was set at p < 0.05.Results:RA patients demonstrated significantly elevated ESR and CRP levels compared to controls (P < 0.001). RF and Anti-CCP were exclusively positive in patients, with none of the controls testing positive (P < 0.001), indicating strong diagnostic value. WBC, IL-17, and IL-21 levels showed no statistically significant differences, although patients exhibited a mild non-significant increase Conclusion:ESR, CRP, RF, and Anti-CCP proved to be highly informative markers for differentiating RA patients from healthy individuals. Conversely, WBC, IL-17, and IL-21 demonstrated limited value when used alone.